Ocular glioma in dog: Case report - Tarcísio Guerra Guimarães; Nuno Santos; Tiago Neves; Luis Flávio Vani Amaral; Paulo Pimenta; Karla Menezes Cardoso (Pubvet, 2021)
The objective is to report the case of a Transmontano Mastiff dog, eight year old intact male, 88 kg, with history of visual loss, diffuse corneal edema and secondary glaucoma. The ocular ultrasound examination revealed a hyperechoic structure located in the peripapillary region of the optic nerve, showing an image compatible with intraocular neoplasia. The animal was submitted to the enucleation procedure and anatomopathological analysis of the affected eye was performed. Histological examination revealed glioma of the optic nerve, considering that neoplasms that affect the retina and optic nerve are rarely described in veterinary medicine, as the case presented.